VD_FINDINFO Pron / 2009 / 70 vom 16. Dezember 2009 - VD Tribunal cantonal (2009)
DÉCISION D'IRRECEVABILITÉ, CURATELLE DE REPRÉSENTATION | 308 al. 2 CC, 309 al. 1 CC, 17 al. 1 CPC, 464 al. 2 CPC, 489 CPC